Incidence, Patient-Related Risk Factors, and Outcomes of Postoperative Pneumonia after Cholecystectomy: A Population-Based Cohort Study. (11th May 2021) - Teng, Yun-Hui; Liu, Fu-Chao; Liu, Keng-Hao; Lin, Jr-Rung; Yu, Huang-Ping
Abstract : Background . Cholecystectomy is one of the most common surgical procedures performed worldwide. The objective of this large, population-based cohort study is to explore the risk factors of pneumonia after cholecystectomy in Taiwan. Methods . From the Taiwanese National Health Insurance Research Database, we selected all patients who underwent cholecystectomy by using ICD-9-codes, from January 1, 1998, to December 31, 2016. The patients were separated into two groups based on the presence or absence of postoperative pneumonia. Basic information, comorbidities, and postoperative complications were evaluated using a t -test or chi-square test. There were 6056 patients in the pneumonia group and 24224 patients in the control group. These two groups were shown in a ratio of 1 : 4 and were matched by age and sex. The log-rank test was used to examine differences in postoperative mortality between patients with and without pneumonia. Preoperative risk factors were analyzed using logistic regression analysis, after adjusting for age and sex. Results . The final dataset included 282184 cholecystectomy patients. Of these patients, 6056 (2.15%) had postoperative new-onset pneumonia. The patient-related risk factors for pneumonia after cholecystectomy in the order of relevance were chronic obstructive pulmonary disease, congestive heart failure, cerebrovascular disease, diabetes mellitus, surgical type, hemodialysis, coronary artery disease, and liver cirrhosis. Compared to patients without postcholecystectomy pneumonia, those with postcholecystectomy pneumonia had higher rates of mortality (within first month, 1.72% vs. 2.28%, P < 0.005 ) and admission to intensive care unit (15.02% vs. 41.80%, P < 0.0001 ) and longer hospital stays (10.71 vs. 18.55 days, P < 0.0001 ). Conclusion. Our results show that postcholecystectomy associated with pneumonia had higher rates of morbidity and mortality in this clinical population. Early identification and possible management of risk factors for pneumonia could improve outcomes of cholecystectomy and lower the risk for patient comorbidities after surgery.